MATERIALISTIC LIFESTYLE IN F. SCOTT FITZGERALD'S THE GREAT GATSBY: A SOCIOLOGICAL APPROACH - KUSUMANINGRUM , ISMI (2007)
The object of this research is the novel entitled The Great Gatsby by F. Scott Fitzgerald. He is one greatest of America writers and socialist critics. The major problem of this study is how materialistic life-style is reflected in the novel The Great Gatsby by F. Scott Fitzgerald is based on a sociological approach. It happen s because in America, in early twen tieth century they have dream called American dream. American dream make s people in America become materialistic life-style. The researcher employs qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is the novel itself. The secondary data sources are the sociological book, some books about American civilization and the other sources related to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the social historical background of American society at early twentieth century, materialistic life-style happened in American society; they have dream to get wealthy, prosperity, money, glamour, and social status. They try to get wealthy by doing anything whether it is legal or illegal. The author wishes to say that materialistic does not guarantee people get happy life. Happiness my occurs when people can live with someone whom they love, and live in peace, friendship, and love.